Quenching process in an ionizing particle track for organic crystalline scintillation detectors - Galunov, N.Z.; Seminozhenko, V.P.; Martynenko, E.V.; Tarasenko, O.A. (Вопросы атомной науки и техники, 2013)
The processes of primary energy exchange of ionizing radiation in track regions of organic molecular scintillation crystalline materials are reviewed. The semi-empirical description of the processes of primary energy exchange of ionizing radiation, which takes into account quenching in a track for organic crystalline scintillators, is discussed. Parameters of this description characterize the primary quenching effect in a track. The revised model of the scintillation process was obtained due to taking into account the influence of polarization interaction between excess charge states and molecules of a substance in the track area.